Oxygen Reduction Reaction at Single‐Site Catalysts: A Combined Electrochemical Scanning Tunnelling Microscopy and DFT Investigation on Iron Octaethylporphyrin Chloride on HOPG. Issue 15 (5th August 2021) - Facchin, Alessandro; Zerbetto, Mirco; Gennaro, Armando; Vittadini, Andrea; Forrer, Daniel; Durante, Christian
Abstract: Here, we investigate the electrochemical activity of a highly oriented pyrolytic graphite (HOPG) supported iron octaethylporphyrin chloride film as a working electrode for the oxygen reduction reaction in 0.1 M HClO4 electrolyte. A voltammetric investigation indicated a quasi‐reversible electron transfer for the Fe III /Fe II redox process, which turned out to be responsible for a "redox catalysis like" mechanism, in which the reduction of the metal center is first required to allow the O2 reduction. Here we proved that O2 is mostly reduced to H2 O in a tetraelectronic process, as evidenced by a rotating ring‐disk electrode (RRDE). Furthermore, electrochemical scanning tunnelling microscopy (EC‐STM) is used as in operando technique for probing the electrode surface at the atomic level while the oxygen reduction reaction occurs, obtaining information on the molecule adlayer electronic and topographic structures. This allows us to follow the change in redox state from Fe III to Fe II induced by the change of the electrode potential in O2 saturated electrolyte. The adsorption of O2 at the iron center was visualized and its depletion upon the application of a potential at which O2 can be reduced. The ORR process catalyzed by FeOEP adsorbed on HOPG was modelled by combining density functional theory, molecular dynamics, and thermodynamics data. Abstract : Fe‐octaethylporphyrin chloride adsorbed on a highly oriented pyrolytic graphite (HOPG) substrate was characterized regarding its ability to catalyze the oxygen reduction reaction using electrochemical scanning tunnelling microscopy under potential control in 0.1 M HClO4 . The data were validated by density functional theory and molecular dynamics experiments with the aim to obtain information about the O2 adsorption/reduction and mechanism process.